Nitrogen, potassium, calcium and sulfur omission in grass Convert - Miranda, Rafaela Pereira; Pietroski, Marizane; Matos, Fabiano Bernardo; Seben Junior, Getulio Freitas; Caione, Gustavo (Comunicata Scientiae, 2018)
Intensive use of Brazilian pastures without the maintenance of soil fertility has decreased their productivity and favoring the onset of symptoms of nutritional deficiency. The objective of this study was to evaluate the effect of nitrogen, potassium, calcium and sulfur omission in symptomatology, growth and dry mass accumulation in grass Convert. The experiment was conducted in a greenhouse with a completely randomized design, with five treatments and four replications. The treatments were: full nutrient solution, nitrogen omission (N), potassium omission (K), calcium omission (-Ca) and sulfur omission (S). The variables were the number of tillers, leaf number, root size, shoot height, characterization of symptoms of deficiency and shoot and root dry mass accumulation. The data were submitted to the F test by analysis of variance and comparison of means by Tukey’s test (p <0.05). The omission of N, K, Ca and S limited the development of Convert grass compared to the full nutrient solution treatment, reducing the number of leaves, tillers, height, root size and dry mass production. The nutrient omission modified forage morphology, showing visual symptoms of deficiency of each nutrient evaluated. The decreasing order of onset of symptoms was N, Ca, S and K.